Metamorphic evolution of a subduction complex, South Shetland Islands, Antarctica - Trouw, RAJ; Simoes, LSA; Valladares, C. S. (Blackwell Science, 1998)
A subduction complex composed of ocean floor material mixed with arc-derived metasediments crops out in the Elephant Island group and at Smith Island, South Shetland Islands, Antarctica, with metamorphic ages of 120-80 Ma and 58-47 Ma? respectively. Seven metamorphic zones (I-VII) mapped on Elephant Island delineate a gradual increase in metamorphic grade from the pumpellyite-actinolite facies, through the crossite-epidote blueschist facies, to the lower amphibolite facies. Geothermometry in garnet-amphibole and garnet-biotite pairs yields temperatures of about 350 degrees C in zone III to about 525 degrees C in zone VII. Pressures were estimated on the basis of Si content in white mica, Al2O3 content in alkali amphibole, Na-M4/Al-IV in sodic-calcic and calcic amphibole, Al-VI/Si in calcic amphibole, and jadeite content in clinopyroxene. Mean values vary from about 6-7.5 kbar in zone II to about 5 kbar in zone VII. Results from the other islands of the Elephant Island group are comparable to those from the main island; Smith Island yielded slightly higher pressures, up to 8 kbar, with temperatures estimated between 300 and 350 degrees C. Zoned minerals and other textural indications locally enable inference of P-T-t trajectories, all with a clockwise evolution. A reconstruction in space and time of these P-T-t paths allows an estimate of the thermal structure in the upper crust during the two ductile deformation phases (D-1 & D-2) that affected the area. This thermal structure is in good agreement with the one expected for a subduction zone. The arrival and collision of thickened oceanic crust may have caused the accretion and preservation of the subduction complex. In this model, D-1 represents the subduction movements expressed by the first vector of the clockwise P-T-t path, D-2 reflects the collision corresponding to the second vector with increasing temperature and decreasing pressure, and D-3 corresponds to isostatic uplift accompanied by erosion, under circumstances of decreasing temperature and pressure.
Keywords: accretionary wedge; geothermobarometry; P-T-t paths; Sanbagawa type metamorphism